An interpretation of the causes of the military rebellion against the imperial order in Brazil in the 1880s - Saes, Guillaume Azevedo Marques de (Pontifícia Universidade Católica de São Paulo, 2013)
The purpose of this article is to analyze the reasons and the motivations of the military officers who rebelled against the imperial regime in Brazil in the 1880s. We attempt to show that behind the military movement that overthrew the monarchy in 1889 there was a contradiction between, on the one hand, the social, professional and ideological profile of the revolutionary officers and, on the other hand, the nature of the imperial regime and the social and economic interests this regime represented and advocated on behalf of.